Buku ajar vogel kimia analisis kuantitatif anorganik (vogel's texbook of quantitative inorganic analysis including elementary instrumental analysis) - Pudjaatmaka, A. Hadyana (EGC, 2013)
xii, 1052 hlm.; Ilus.; 25 cm.